Parental Stress in Home Education: A Case in the Philippines - Pastoril, Julie Marie; Flores, Maude Adan; Derecho, Mia Janice; Etcuban, Jonathan (British Journal of Teacher Education and Pedagogy, 2024)
Parents had to deal with more stress during the COVID-19 epidemic as they balanced employment and at-home schooling. Many found it difficult to provide emotional support, adjust to new technology, and balance their children’s academic demands. This revolutionary change put parental engagement to the test, frequently causing family relations to break down due to the stress of running home-based learning environments. This study aimed to determine the degree of parental stress in home education during the COVID-19 pandemic in the three identified public elementary schools in Cebu, Philippines, as a basis for crafting an action plan. This study was conducted by 150 parents whose children are enrolled in the three identified public elementary schools. It utilized a descriptive correlational method using an adapted survey questionnaire based on the study of Vermulst et al. (2011). The collected data were statistically treated using frequency, mean, standard deviation, Chi-square test of independence, and ANOVA. The study revealed a significant relationship between the respondents’ gender and stress levels. Also, the study shows that the degree of stress the respondents experienced differs when grouped by income. It is concluded that gender is associated with stress among parents. Mothers and fathers are relatively stressed about parenting amid the pandemic due to gender roles. Because of the pandemic, many families have exhausted the available resources to meet their daily needs. Each household has different needs, available resources, and support from the community. Thus, stress levels and coping strategies among parents and families also differ. The researchers highly recommend implementing the proposed action plans to address families’ hurdles in parenting children at home.